Some Reactions with 3-Chloro-4-cyano-5,6-diphenyl Pyridazinone - Said, S.A.; Hamad, M.M.; El-Gendy, A.M. (Asian Journal of Chemistry, 2010)
Treatment of 4-cyano-5,6-diphenyl 2(1H) pyridazinone with POCl3/ PCl5 mixture gave 3-chloro-4-cyano-5,6-diphenyl pyridazine (I). The reactions of compound (I) with primary amines, hydrazine hydrate, 2-cyano-ethanoic acid hydrazide, thiourea, sodium methoxide, sodium azide, sodamide and/or active methylene compounds have been studied. Also the reactions of 3-amino-4,5-diphenyl-1H pyrazolo (3,4-c) pyridazine (III) with picric or salicylic acids, aromatic aldehydes, α-dicarbonyl compounds and/or 3-nitrophthalic anhydride have been investigated.